Tubercular Lymphadenitis: As a Rare Cause of Obstructive Jaundice - Rajat Jhamb; Abhishek Juneja; SV Madhu; S Giri (Annals of Cytology and Pathology - Peertechz Publications, 2016)
Obstructive jaundice is an extremely rare presentation of abdominal tubercular lymphadenitis. We hereby report a case of obstructive jaundice in an adult female, occurring as a result of periportal and peripancreatic tubercular lymphadenitis causing compression of the biliary tract. A 42-year-old female patient presented with fever for two months and jaundice for 15 days. Contrast enhanced computed tomogram of the abdomen showed periportal, peripancreatic, gastro-hepatic, and retroperitoneal lymphadenopathy with caseation. Provisional diagnosis of abdominal tubercular lymphadenitis was made. Anti-tubercular drugs which are safe in hepatitis were started. Magnetic resonance cholangiopancreatography (MRCP) was done in view of worsening of liver function tests and development of clinical features of obstructive jaundice during hospital stay. Confluent lymph nodal mass showing necrotic areas was seen in the hepatogastric, portal, peripancreatic, retropancreatic and portocaval region pushing the pancreas and portal vein anteriorly on magnetic resonance cholangiopancreatography. In view of the clinical deterioration on treatment, ultra-sonography guided fine needle aspiration cytology was also done which revealed chronic granulomatous inflammation.AFB stain did not demonstrate acid-fast bacilli. Though obstructive jaundice secondary to abdominal tubercular lymphadenitis is rare, it should be considered as a differential diagnosis in TB endemic area.